The diagnostic and prognostic value of serum endocan in patients with cirrhotic cardiomyopathy - Voiosu Andrei Mihai; Bălănescu Paul; Daha Ioana; Smarandache Bianca; Rădoi Aurelia; Mateescu Radu Bogdan; Băicuş Cristian Răsvan; Voiosu Theodor Alexandru (Sciendo, 2018)
Background. We aimed to determine the relationship between endocan and cirrhotic cardiomyopathy.